The psychology of parental control : how well-meant parenting backfires - Grolnick, Wendy S. (L. Erlbaum Associates, 2003)
What is parental control? Is it positive or negative? Are there alternatives to control and how might we apply them? This book addresses these and other questions about the meaning and predictors of parental control, as well as its consequences for children's adjustment and well-being.